Syngas Production from Combined Steam and Carbon Dioxide Reforming of Methane over Ce-modified Silicasupported Nickel Catalysts - Siang, Tan Ji; Danh, Huong T.; Singh, Sharanjit; Truong, Quang Duc; Setiabudi, H. D.; Vo, Dai-Viet N. (The Italian Association of Chemical Engineering-AIDIC, 2017)
This study investigates the physicochemical attributes of Ce-modified Santa Barbara Amorphous-15 (SBA-15) supported Ni catalyst and evaluates its catalytic performance for combined steam and CO2 reforming of methane in order to produce synthesis gas. Both 10 % Ni/SBA-15 and 10 % Ni/Ce-SBA-15 catalysts were prepared by conventional wetness impregnation method and characterised via Brunauer-Emmett-Teller (BET) surface area, H2 temperature-programmed reduction (H2-TPR) and X-ray diffraction (XRD) techniques. Both 10 % Ni/Ce-SBA-15 and 10 % Ni/SBA-15 catalysts possessed high BET surface area of 595.04 m2 g-1 and 493.73 m2 g-1. XRD measurement revealed the existence of NiO phase with crystallite sizes of 15.5 nm and 13.6 nm for the corresponding 10 % Ni/SBA-15 and 10 % Ni/Ce-SBA-15 catalysts whilst cerium (IV) oxide (CeO2) particles were well dispersed on the mesoporous SBA-15 support surface. H2-TPR results showed that NiO to Ni0 reduction was completely obtained at temperature beyond 800 K and the reduction temperature was contingent on the degree of metal-support interaction associated with size and location of NiO nanoparticles on support. Ce-modified catalyst was more stable and active than unmodified Ni/SBA-15 catalyst. 10 % Ni/Ce-SBA-15 catalyst exhibited a significant enhancement in CH4 conversion (up to 11.06 %) and H2 yield (30.51 mol%) reasonably due to the high oxygen storage capacity and redox property of CeO2 phase incorporated into the mesoporous framework of SBA-15 support. H2/CO ratio of 10 % Ni/Ce-SBA-15 catalyst was stable at about 1.74 while a lower value of 1.14 was observed for 10 % Ni/SBA-15 catalyst indicating the occurrence of parallel reactions including CH4 steam reforming reaction and CH4 dry reforming reaction.